Magnesium Transporter MGT6 Plays an Essential Role in Maintaining Magnesium Homeostasis and Regulating High Magnesium Tolerance in Arabidopsis - Yan, Yu-Wei; Mao, Dan-Dan; Yang, Lei; Qi, Jin-Liang; Zhang, Xin-Xin; Tang, Qing-Lin; Li, Yang-Ping; Tang, Ren-Jie; Luan, Sheng (Frontiers in Plant Science, 2018)
Magnesium (Mg) is one of the essential nutrients for all living organisms. Plants acquire Mg from the environment and distribute within their bodies in the ionic form via Mg2+-permeable transporters. In Arabidopsis, the plasma membrane-localized magnesium transporter MGT6 mediates Mg2+ uptake under Mg-limited conditions, and therefore is important for the plant adaptation to low-Mg environment. In this study, we further assessed the physiological function of MGT6 using a knockout T-DNA insertional mutant allele. We found that MGT6 was required for normal plant growth during various developmental stages when the environmental Mg2+ was low. Interestingly, in addition to the hypersensitivity to Mg2+ limitation, mgt6 mutants displayed dramatic growth defects when external Mg2+ was in excess. Compared with wild-type plants, mgt6 mutants generally contained less Mg2+ under both low and high external Mg2+ conditions. Reciprocal grafting experiments further underpinned a role of MGT6 in a shoot-based mechanism for detoxifying excessive Mg2+ in the environment. Moreover, we found that mgt6 mgt7 double mutant showed more severe phenotypes compared with single mutants under both low and high Mg2+ stress conditions, suggesting that these two MGT-type transporters play an additive role in controlling plant Mg2+ homeostasis under a wide range of external Mg2+ concentrations.